Pengaruh Ditutupnya Tiktok Shop Terhadap Consumer Shopping Behavior - Anggi Setiawan; Immanuela Irene Harmany (Riviera Publishing, 2025)
This essay aims to look at the effect of TikTok's closure on consumer shopping behavior. The rapid development of technology affects the way, style, behavior and habits of people in carrying out daily activities. One of the most pronounced technological developments and the most influential on our lifestyle is the development of digital technology. Over time, the application of digital technology in an effort to facilitate human activities has unwittingly changed the lifestyle of many people. Many digital platforms have emerged with various features and functions as a means to achieve these goals. One of the most widely used digital platforms today is e-commerce, a digital platform where customers can conduct online buying and selling transactions through mobile devices. One of the e-commerce platforms with the most rapid development as well as controversial some time ago is TikTok Shop, one of the features of TikTok social media that allows people to make buying and selling transactions on the platform. TikTok Shop with its various pros and cons from both the public and the government makes us want to research further related to the closure of TikTok Shop and changes in consumer behavior in shopping.